El enfoque intercultural y la identidad cultural de los alumnos de la Institución Educativa 10324 caserío de Patipampa, región Cajamarca - Estrella Pérez, Cheyla (2022)
The objective of the research project was to analyze how the intercultural approach is incorporated and how this at the same time influences the construction of the cultural identity of the students from 1st to 6th grade of the Educational Institution 10324, located in the Patipampa farmhouse, Cutervo province, Cajamarca region, year 2021. It is a purely qualitative descriptive study, two anthropological currents were proposed for interpretation, historical particularism and cultural relativism, in addition, the ethnographic, historical - comparative and deductive - inductive. This research was carried out in a multigrade educational institution and the sample was 03 teachers and 28 boys and girls, in total. The main instruments for data collection were the interview, survey and review of documentary files. The results were processed through tables and a detailed review of curricular documents.